De Jong Gierveld Loneliness Scale - Short Version: Validation for the Brazilian Context - Coelho, Gabriel Lins de Holanda; Fonseca, Patrícia Nunes da; Gouveia, Valdiney Veloso; Wolf, Lukas Jarmo; Vilar, Roosevelt (Paidéia (Ribeirão Preto), 2018)
Individuals who experience a state of loneliness may feel that their needs of belonging are unfulfilled, suffering a state of social deprivation that might affect their well-being. For a better understanding, three studies (N = 939) aimed to adapt the short version of the De Jong Gierveld Loneliness Scale to Brazil. In Studies 1 and 2, exploratory and confirmatory analyses corroborated the expected two correlated factors structure: emotional and social. Evidences of convergent validity and factorial invariance between genders were also observed. Study 3 verified the instrument’s psychometric properties through Item Response Theory (IRT) and the results showed that the items presented acceptable levels of difficulty, discriminated participants with similar levels of aptitude/endorsement and indicated that both factors of the measure presented substantial information for a wide range of the latent trait. We conclude that this measure is psychometrically suitable for use in Brazil.